Impact of Regulatory Change on Income Smoothing and Earning Distortions? Evidence from a Univariate Approach: (Acta Universitatis Danubius. Œconomica, 2024)
: The issue on how some managers misstate and manipulate their financial positions by underestimating or overestimating actual economic items has continued to draw attention. Research presents evidence that a change in accounting standards has implication for the reduction in such manipulations. Using evidence from in South Africa, this paper applies univariate analysis to examine whether there is difference between earnings manipulations during two accounting regulatory regimes – Generally Acceptable Accounting Practices (GAAP) and the International Financial Reporting Standards (IFRS). To ensure robustness, the paper used two measures of financial report manipulations – income smooth and earnings management. The finding confirms that the adoption of IFRS caused, to some extent a reduction in discretional income smoothing and earnings distortion. Furtherance, the outcome is robust and not sensitive to the methods applied for the test; thus, the evidence can be used to make informed policy decisions. The result has implication for regulation, policy making and modification of extant Standards.